Healthy Ageing A Capability Approach to Inclusive Policy and Practice - Stephens, Christine (Routledge Studies in Modern History, 2019)
What does it mean to age well? This important new book redefines what 'successful' ageing means, challenging the idea that physical health is the only criteria to gauge the ageing process and that an ageing population is necessarily a burden upon society. Using Sen's Capability Approach as a theoretical starting point Healthy Ageing: A Capability Approach to Inclusive Policy and Practice outlines a nuanced perspective that transcends the purely biomedical view, recognising ideas of resilience, as well as the experiences of older people themselves in determining what it means to age well. It builds to provide a comprehensive response to the overarching discourse that successful ageing is simply about eating well and exercising, acknowledging not only that older people are not always able to follow such advice, but also that well-being is mediated by factors beyond the physical. In an era where ageing has become such an important topic for policy makers, this is a robust and timely response that examines what it means to live well as an older person. It will be hugely valuable not only for students of gerontology and social care, but also professionals working in the field.